Thor. Vol. 4, God of hammers - Cates, Donny (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2022)
"Mjolnir, the powerful Uru hammer that Thor has wielded in battle for centuries, has gone missing! And nobody, not even the all-seeing Lady Sif, is able to locate it. So Thor must turn to the last person he wants help from: Odin. For until the hammer is found, nobody is safe! Because it turns out that Mjolnir is on a rampage across the Ten Realms -- leaving only death and destruction in its path! The fatal prophecy of the God of Hammers is about to be unleashed, and Thor must act fast to save his kingdom! Donny Cates continues his action-packed Asgardian saga, and artist Nic Klein is back for twists and turns that not even the All-Father can possibly be ready for!"--